Ab Initio Study of Atropisomers of Derivatives of N-Benzyl-2-phenylpyridinium Ions - Firouzeh Nemati; Hossein Kiani (E-Journal of Chemistry)
Ab initio calculation at RHF/6-31G* level of theory for geometry optimization of conformers of N-benzyl-2-phenylpyridinium ions are reported. The series of electron-withdrawing and electron-donating groups have been replaced by 3-H phenyl and benzyl of N-benzyl-2-phenylpyridinium ions and the energy difference between the syn- and anti- forms discussed in terms of π-π stacking.